Arabs face the modern world religious, cultural, and political responses to the West - Rejwan, Nissim 1924- (Univ. Press of Florida, 1998)
The book begins with reactions to the West in the works of such religious leaders as Afghani, 'Abduh, Al-Kawakibi, Rashid Rida, Qasim Amin, and Taha Husain; the rise of Islamic militancy; and the spread of the nationalist movement. It describes events surrounding the Six-Day War of 1967 and the October War of 1973 and the rise of a new and more violent type of religious fundamentalism. And it summarizes issues that continue to preoccupy Muslim Arabs into the late 1990s - prospects for democracy, the position of women, changing attitudes toward Israel, and the plight of intellectuals in the face of rising militancy. Rejwan, a Baghdad-born Israeli, brings to this study an intimate knowledge of modern Arabic culture on a popular level, producing a synthesis of history, politics, theology, and feminist currents from the standpoint of an insider/outsider.
Keywords: Geschichte 1900-2000; Geschichte 1870-1997; Arabieren; Civilisation arabe - Influence occidentale; Culturele aspecten; Islam et politique - États arabes; Islam; Oorlogen; Orient et Occident; Politieke aspecten; Kultur; Politik; Civilization, Arab -- Western influences; East and West; Islam and politics -- Arab countries; Araber; Kulturkontakt; États arabes - Politique et gouvernement - 1945-; États arabes - Vie intellectuelle - 20e siècle; Arab countries -- Politics and government -- 1945-; Arab countries -- Intellectual life -- 20th century; Europa